Pengaruh Content Marketing dan endorsment terhadap Kepuasan Pelanggan dengan Keputusan Pembelian sebagai Variabel Intervening pada Shopee : (Studi Kasus pada Mahasiswa Manajemen UPI YPTK Padang Angkatan 2020) - Khaira Septia Annisa; Yulasmi Yulasmi; Mardhatila Fitri Sopali (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study titled Influence of Content Marketing and Endorsement on Customer Satisfaction with Purchasing Decisions as an intervening variable in shopee (Case Study In Management Students of UPI YPTK Padang Angkatan 2020). The purpose of this study was to know and try to analyze the Effect of Content Marketing and Endorsement on Customer Satisfaction with Purchasing Decisions as an intervening variable on shopee (Case Study In Management Students of UPI YPTK Padang Angkatan 2020). The study is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. Data collection methods were through interviews and circulating questionnaires, with a sample of 88 respondents. The results of the study found. There is a positive and significant influence of content marketing on Shopee's Customer Satisfaction. There is a positive and significant influence of content marketing on Shopee's purchasing decisions. There is no positive and insignificant influence of Endorsement on Customer Satisfaction on Shopee. There is a positive and significant influence between Endorsement and Purchase Decisions on Shopee. There is a positive and significant influence between Purchase Decisions on Customer Satisfaction on Shopee. Content Marketing mediates Purchase Decisions to Customer Satisfaction on Shopee. Endorsement mediates Purchase Decisions to Customer Satisfaction on Shopee.